The Effect of Brand Equity and Service Quality on Purchase Decisions on the Blibli.Com Online Shopping Platform - Rahma Mustafida Husna; Nabilah Auradifa Aditya Putritami; Ana Nur Khasanah; Zulfa Fahmy; Khairani Zikrinawati (Experimental Student Experiences, 2024)
The purpose of this research is to find out the contribution and relevance of brand equity and service quality on the Blibli platform to the purchasing decisions of Blibli users. This research uses a quantitative approach. In this study, data was collected by distributing questionnaires. Data is assessed using a Likert scale with four alternative answers. Data analysis techniques used in this study include validity and reliability tests, hypothesis testing, partial tests, and simultaneous tests. With a calculated t value of 6.639 > 1.984 from t table and a p value of 0.001 <0.05, the multiple linear regression analysis test shows that brand equity has a significant influence on purchasing decisions. With a calculated t value of 6.011 > 1.984 from t table and a p value of 0.001 <0.05, service quality makes a significant contribution to purchasing decisions by 84.3%. The results of the Anova test show that brand equity and service quality variables contribute to purchasing decisions on the Blibli platform. This explains how important brand equity and service quality are for a company or product. Frequent evaluations, especially on factors such as brand equity and service quality, can help business development.